Los "Empates" y la Memoria del Caucho - Pizarro-Romero, A (Universidad de Chile, Facultad de Filosofia y Humanidades, Departamento de Literatura, 2014)
The empates are non-violent strategies of resistance devised by the inhabitants of the Brazilian Amazonia in order to stop the threatening advance of companies that are invading and deforesting their environment. This research attempts to demonstrate how this confrontation is informed by a collective memory in which it is possible to identify echoes of three crucial moments in this region s history of rubber: the extraction of rubber at the end of the 19th and the beginning of the 20th century; the "Battle of Rubber", declared by the government of Getúlio Vargas during World War II; and the struggles of Acre in the 1970 s, which marks the beginning of the strategy of empates. We find, at the core of this collective memory, not only oral tradition but also silence.